2020
DOI: 10.5435/jaaos-d-19-00751
|View full text |Cite
|
Sign up to set email alerts
|

Readmission Rates After Hip Fracture: Are There Prefracture Warning Signs for Patients Most at Risk of Readmission?

Abstract: Background: The purpose of this study was to evaluate known and yet unknown risk factors associated with readmission to the hospital within 30 days after hip fracture. Methods: In this study, we used the Cerner Health Facts Electronic Health Record database data from January to August 2015. The univariate association of each variable (discharge location, demographic details, and comorbidities) against the 30-day readmission status was evaluated using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In their multicenter database study, Checketts et al reported that male patients were more likely to be readmitted than female patients after HFx [ 20 ]. The same study by Checketts et al reported a possible ceiling effect of age on readmission rates, with older patients having a higher risk prior to 75 years, whereas after 75 years the association became stable [ 20 ]. While our data was significant for association between age and mortality, it is possible that a similar principle could be applied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In their multicenter database study, Checketts et al reported that male patients were more likely to be readmitted than female patients after HFx [ 20 ]. The same study by Checketts et al reported a possible ceiling effect of age on readmission rates, with older patients having a higher risk prior to 75 years, whereas after 75 years the association became stable [ 20 ]. While our data was significant for association between age and mortality, it is possible that a similar principle could be applied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported 30-day readmission rates for HFx between 10.7% to 11.9% and 90-day readmission rates around 19.7% [ 20 22 ]. Our secondary outcome results are in line with previous literature as 30- and 90-day readmission rates prior to the pandemic were 13.7% and 13.3%, respectively [ 20 22 ]. During the pandemic, our 30- and 90-day readmission rates were 12.4% and 7.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 By gaining a better understanding of the risk factors of patients who experience readmission, it is possible to focus on improving the quality of care and reducing the cost of care for these at-risk populations. 7,11 Our study evaluates the Nationwide Readmissions Database to examine readmission rates after cervical spinal fusion. Using this database, we evaluate both known and currently unknown risk factors associated with readmission to the hospital within 90 days following initial discharge.…”
mentioning
confidence: 99%